Expression of Ferroptosis-Related Genes Shapes Tumor Microenvironment and Pharmacological Profile in Gastric Cancer - Xiao, Shilang; Liu, Xiaoming; Yuan, Lingzhi; Chen, Xiao; Wang, Fen (Frontiers in Cell and Developmental Biology, 2021)
Abstract Background: Ferroptosis is a form of regulated cell death that occurs as a consequence of lethal lipid peroxidation. A wealth of studies has demonstrated that ferroptosis profoundly modulated numerous biological behaviors of tumor. However, its natural functions in gastric cancer (GC) remain to be explored. Methods: Firstly, a total of over 1000 gastric cancer patients from Gene Expression Omnibus (GEO) and the Cancer Genome Atlas (TCGA) database were included in our study. Secondly, 32 ferroptosis-related genes were extracted from ferrDb website. Then, the unsupervised clustering was performed to classify patients into three distinct ferroptosis-related clusters. Subsequently, we systematically and comprehensively explored the biological characteristics of each cluster. Finally, we constructed a scoring system named ferroptosis score to quantify each cluster, and also investigated the predicatively therapeutic value of ferroptosis score for chemotherapy and immunotherapy. Results: Based on the expression of 32 ferroptosis-related genes, three distinct ferroptosis-related subtypes with various biological characteristics were determined. Integrated analysis showed that cluster1 was a microsatellite-instable-like (MSI-like) subtype, cluster2 was an epithelial-mesenchymal-transition-like (EMT-like) subtype, while cluster3 tended to be metabolic-like subtype. Prognostic analysis revealed that patients in cluster2 had a worse overall survival and relapse-free survival. The distribution of ferroptosis score was significantly different in clusters and geneclusters. Ferroptosis score could predict biological characteristics of each cluster, stromal activity and progression of tumor. Low ferroptosis score group was characterized by activation of antigen processing and presentation, DNA damage repairing pathways, and metabolic pathways, while high ferroptosis score group was characterized by stromal activation. In response to anti-cancer drugs, ferroptosis score was highly negatively associated with drugs targeting MAPK signaling and PI3K/MTOR signaling, while positively correlated with drugs targeting cell cycle, mitosis and metabolism. Finally, we also proved that ferroptosis score could serve as a reliable biomarker to predict response to immunotherapy. Conclusion: This work revealed that tumor cells as well as their surrounding microenvironment could be shaped by varying activation degrees of ferroptosis. Establishing ferroptosis-related subtypes would guide us to predict biological features of individual tumor and select appropriate treatment protocol for patients.